2022
DOI: 10.3389/fphar.2022.1029088
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological evidence of the chang-yan-ning formula in the treatment of colitis

Abstract: Ulcerative colitis (UC) is a subtype of inflammatory bowel disease (IBD) and occurs mainly in the colon. The etiology of UC is rather complex and involves various pathological factors, including genetic susceptibility, dietary intakes, environment, and microbiota. In China, the Chang-Yan-Ning (CYN) formula has been utilized in the clinic to treat gastrointestinal disorders, but its pharmacological evidence remains elusive. The investigation was designed to explore the molecular and cellular mechanisms of CYN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Essential oil from Liquidambar formosana leaves has certain anti-in ammatory activity, which can ameliorates in ammatory response in lipopolysaccharideactivated mouse macrophages [31] .The remarkable clinical e cacy of CYN tablets may come from the comprehensive effect of multi-components and multi-targets of different herbs. Identi cation and analysis using liquid chromatography-tandem mass spectrometry (LC-MS) revealed that the main active components of CYN (a TCM formula) include quercetin, gallic acid, catechol, luteolin, kaempferol, etc., which possess various biological activities such as anti-in ammatory, visceral pain relief, antioxidant, alleviation of visceral hypersensitivity, and modulation of gut microbiota [32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Essential oil from Liquidambar formosana leaves has certain anti-in ammatory activity, which can ameliorates in ammatory response in lipopolysaccharideactivated mouse macrophages [31] .The remarkable clinical e cacy of CYN tablets may come from the comprehensive effect of multi-components and multi-targets of different herbs. Identi cation and analysis using liquid chromatography-tandem mass spectrometry (LC-MS) revealed that the main active components of CYN (a TCM formula) include quercetin, gallic acid, catechol, luteolin, kaempferol, etc., which possess various biological activities such as anti-in ammatory, visceral pain relief, antioxidant, alleviation of visceral hypersensitivity, and modulation of gut microbiota [32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Liquid chromatography coupled with tandem mass spectrometry analysis revealed that the primary constituents of CYN are gallic acid, methyl gallate, catechol, asperulosidic acid, kaempferol, and quercetin [ 89 ]. Animal studies showed that CYN reduces the levels of pro-inflammatory cytokines in the serum of a murine colitis model, downregulating IL-17 and HIF-1α and upregulating PPARγ and CCL2 in the colon, facilitating the alternative activation of peritoneal macrophages [ 90 ]. Additionally, CYN treatment has been shown to enhance the diversity and richness of the intestinal microbiota in UC mice, while restoring the metabolic profile during colitis [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, CYN tablets have been proven effective for the treatment of diarrhea, acute gastroenteritis, and ulcerative colitis. [14][15][16] When we screened the anti-EV71 medicines, we found by chance that the aqueous solution of CYN tablets has in vitro anti-EV71 effects. The 2020 edition of the Chinese Pharmacopoeia records that CYN tablets have the effects of clearing heat and relieving dampness, which is consistent with the therapeutic principle of HFMD.…”
Section: Introductionmentioning
confidence: 99%